CAMELLIA THUONGIANA - A NEW YELLOW CAMELLIA SPECIES FROM VIETNAM - Lương Văn Dũng; Le Anna; Nguyễn Thị Hạnh; Nguyễn Thị Liễu (Tạp chí Khoa học Đại học Đà Lạt)
Camellia thuongiana Luong, Anna Le & Lau (Theaceae), a new yellow Camellia species from Doanket commune, Dahuoai district, Lamdong province, is described and illustrated. Based on morphological data we affirm that this new species belong to section Chrysantha.